Damping characteristic analysis of grid-forming PMSG-based WT under different power oscillation damping controls - Xiaotian Yuan; Zhengchun Du; Yujun Li; Tong Qu; Han Jiang (International Journal of Electrical Power & Energy Systems)
In this paper, the damping characteristics of the grid-forming permanent magnet synchronous generator (PMSG)-based wind turbine (WT) under different damping controls are investigated considering energy efficiency. First, a newly developed grid-forming control, the DC voltage synchronization control (DVSC), is incorporated into PMSG-based WT, allowing for inertial response and grid-synchronization of WT without a phase-locked loop (PLL). Then, by analyzing the coupling effects between WT dynamics and the active power loop, it was found that the previous active power-based grid-forming controls may sacrifice maximum power point tracking (MPPT) for damping provision and consequently affect the system damping coefficient. To this end, two cost-effective reactive power-based damping controllers are designed using the internal DC signals, where the reactive power and the stored DC energy are jointly harnessed for damping enhancement. The proposed dampers have the energy-saving merits of not impairing MPPT while providing the same damping support as the active power-based dampers. Furthermore, the impacts of related control parameters and operating conditions on system damping properties are substantially evaluated, followed by the parameter tuning method for balancing the DC voltage stability and damping requirements. Simulation studies are performed under various system contingencies in two distinct sceneries to compare the performance of different damping controllers.© 2017 Elsevier Inc. All rights reserved.